Di-n-butylammonium 2- (3,5-di-tert-butyl-4-hydroxybenzyl)sulfanyl benzoate - Alhadi, A.A.; Olmstead, M.M.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2010)
The title salt, C(8)H(20)N(+)center dot C(22)H(27)O(3)S(-), is a proton-transfer compound derived from the recently reported parent carboxylic acid [Alhadi et al. (2010). Acta Cryst. E66, o1787] by the addition of a second equivalent of di-n-butylamine, yielding the di-n-butylammonium carboxylate salt. The structure of the carboxylate anion resembles that of the parent carboxylic acid. The main difference lies in the position of the H atom in the 4-hydroxy group. In the anion the O-H bond is perpendicular, rather than parallel, to the benzyl ring. This position appears to facilitate hydrogen bonding to an O atom of the carboxylate group of a symmetry-related anion. In addition, there are three N-H center dot center dot center dot O hydrogen bonds. In contrast, the neutral species hydrogen bonds via a carboxylic acid dimer. The dihedral angle between the benzene rings in the anion is 79.19 (7)degrees.